2018
DOI: 10.29129/inujgse.417609
|View full text |Cite
|
Sign up to set email alerts
|

Sınav Kaygısını Azaltmaya Yönelik Bir Psikoeğitim Programının Sekizinci Sınıf Öğrencilerinin Sınav Kaygısına Etkisi

Abstract: The aim of this study is to investigate the effectiveness of the exam anxiety psycho-education program in decreasing the exam anxiety levels of students. Design & Methodology: Experimental design with pre-test and post-test control group was used in the study. The research was conducted on 8 th grade students studying in a secondary school in Malatya province center. There are three groups in the study: the experimental group, the control group and the placebo group and there are 15 students in each group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…According to the results, it can be asserted that the anxiety score change is supported by past studies on the usability of psychoeducation programs in the test anxiety area. It is observed that psychoeducation programs aimed at decreasing test anxiety have obtained similar results and support the present study (Alver et al, 2013;Seçer, 2013;Kaya, 2015;Taşpınar & Başgül, 2017;Karaburç & Tunç, 2017;Genç & Kutlu, 2018;Doğan, 2019;Kral, 2019, Yapan, 2021. As a result of a study conducted by Karaburç & Tunç (2017) on test anxiety, it was observed that the posttest emotionality and worry subscale data of the experimental group individuals were lower than the pretest data.…”
Section: Discussion Conclusion and Recommendationsupporting
confidence: 89%
See 2 more Smart Citations
“…According to the results, it can be asserted that the anxiety score change is supported by past studies on the usability of psychoeducation programs in the test anxiety area. It is observed that psychoeducation programs aimed at decreasing test anxiety have obtained similar results and support the present study (Alver et al, 2013;Seçer, 2013;Kaya, 2015;Taşpınar & Başgül, 2017;Karaburç & Tunç, 2017;Genç & Kutlu, 2018;Doğan, 2019;Kral, 2019, Yapan, 2021. As a result of a study conducted by Karaburç & Tunç (2017) on test anxiety, it was observed that the posttest emotionality and worry subscale data of the experimental group individuals were lower than the pretest data.…”
Section: Discussion Conclusion and Recommendationsupporting
confidence: 89%
“…The increase in anxiety was thought to be associated with limited time until the test, decision of distance education after formal education and uncertainty of the test curriculum. In the literature it was seen that there was no change in the control group posttest data in experimental studies (Alver et al, 2011;Seçer, 2013;Kaya, 2015;Taşpınar & Başgül, 2017;Karaburç & Tunç, 2017;Genç & Kutlu, 2018;Doğan, 2019;Kral, 2019, Yapan, 2021. In addition, the fact that the individuals in the control group did not know the methods of coping with anxiety with the approach of the exam, could not manage the time well in the exams, and could not determine the most efficient study method for themselves while learning the subject they were missing may have caused their anxiety to increase.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaşamda ulaşmak istediğimiz en önemli amaç olan mutluğun (Thoilliez, 2011) sağlanmasında akademik hedeflerin gerçekleşmesinin de önemli olduğu düşünüldüğünde öğrencilerin nitelikli bir okula yerleşebilmek için mücadele etmeleri gerektiği de görülmektedir (Genç & Kutlu, 2018).…”
Section: Introductionunclassified